Early impairment of cognitive functions in Parkinson's disease - Stella, Florindo [UNESP]; Gobbi, Lilian T. B. [UNESP]; Gobbi, Sebastião [UNESP]; Oliani, Merlyn M. [UNESP]; Tanaka, Kátia [UNESP]; Pieruccini-Faria, Frederico [UNESP] (FapUNIFESP (SciELO), 2007)
Background: Impairment in non-motor functions such as disturbances of some executive functions are also common events in Parkinson's disease patients. Objective: To verify the performance of Parkinson's disease patients in activities requiring visuoconstructive and visuospatial skills. Method: Thirty elderly patients with mild or moderate stages of Parkinson's disease were studied. The assessment of the clinical condition was based on the unified Parkinson's disease rating scale (56.28; SD=33.48), Hoehn and Yahr (2.2; SD=0.83), Schwab and England (78.93%), clock drawing test (7.36; SD=2.51), and mini-mental state examination (26.48; SD=10.11). Pearson's correlation and stepwise multiple regression were used for statistical analyses. Results: The patients presented deterioration in visuospatial and visuoconstructive skills. Conclusion: The clock drawing test proved to be a useful predictive tool for identifying early cognitive impairment in these individuals.
Keywords: Cognition disorders; Neuropsychological tests; Parkinson's disease; pramipexole; selegiline; clinical assessment tool; cognitive defect; correlation coefficient; depth perception; early diagnosis; monotherapy; motor performance; neuropsychological test; outcome assessment; Parkinson disease; predictor variable; statistical analysis; Unified Parkinson Disease Rating Scale; Severity of Illness Index; Space Perception; Visual Perception